Impact of e-Satisfaction on Customer Engagement and Loyalty in E-Commerce - Susanta, Susanta; Indarwanta, Didik; Novianti, Dewi; Saptono, Tri (RSF Conference Series: Business, Management and Social Sciences, 2025)
The purpose of this study is to investigate how consumer engagement and e-loyalty are affected by e-satisfaction. Customers in the Yogyakarta Special Region who use the Shopee online platform were the target of this study. Closed questionnaires were used to gather information from Shopee patrons residing in the Special Region of Yogyakarta. 200 Shopee consumers who were chosen according to specific criteria made up the sample size for this study. The analysis tool utilizes WarpPLS. The study’s findings indicate that e-satisfaction has a significant influence on both consumer engagement and e-loyalty, that e-loyalty is significantly impacted by customer engagement, and that e-satisfaction has a significant influence on e-loyalty through customer engagement. These results demonstrate the importance of e-satisfaction and consumer engagement in promoting loyalty.